Hak Mewaris Bagi Ahli Waris Yang Berkebutuhan Khusus Dalam Perspektif Hukum Perdata - Sulastri, Sulastri; Ramadhani, Dwi Aryanti; Sakti, Muthia (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
The inheritance rights of a child who becomes an heir is the main thing to be studied in more depth in this research. Especially when the child who is gifted by God has special needs. As a normal heir or legal subject can be declared legally capable, but how is the legal protection of rights with children with special needs, the question is the first formulation of the two formulations, while the second formulation is how rights and obligations in the perspective of civil law. This research was completed with a normative juridical method, and with a literature review approach, this research method has a descriptive analysis nature, meaning that the two formulations will be explained in detail from the elaboration of primary legal sources and tertiary legal sources. This study concludes that the legal protection of heirs to children with special needs has been regulated in Article 432 of the Civil Code as a fundamental paradigm in the implementation of legal protection. While the rights and obligations obtained need to be facilitated by the concept of guardianship or guardianship, so that the rights and obligations of children with special needs can be accommodated optimally. Keywords: the Heir, Special Needs, Perspective, Civil Law